Case Report: The Added Value of Liquid Biopsy in Advanced Colorectal Cancer From Clinical Case Experiences - Ulivi, Paola; Passardi, Alessandro; Marisi, Giorgia; Chiadini, Elisa; Molinari, Chiara; Canale, Matteo; Pasini, Luigi; Ferroni, Fabio; Frassineti, Giovanni Luca; Bartolini, Giulia; Monti, Manlio (Frontiers in Pharmacology, 2021)
Liquid biopsy represents a valid strategy for tumor molecular characterization. It gives the opportunity to bypass tumor heterogeneity, to monitor tumor characteristics during the course of treatment, and to perform the analysis even when tumor tissue is not available or inadequate. In the clinical practice of metastatic colorectal cancer, tumor molecular characterization is crucial for patient management, as RAS and BRAF status could influence the treatment choice. Although for this type of cancer tumor tissue is usually available at diagnosis, liquid biopsy could give complementary information and could permit monitoring of the mutation status during the course of treatment. At present, there are no clinical indications for its use in clinical practice. However, we report four clinical cases for which liquid biopsy analysis gave integrative information with respect to tumor tissue characterization, which permits us to understand the unresponsiveness of patients to treatment, with potential implications in patient’s management.